Evaluación de la satisfacción de los pacientes de la Clínica de Cirugía Plástica Joseph Duarte de la ciudad de Guayaquil - Saltos Fernández, Karen Julieth (2023)
The purpose of this project is to solve the existing problem within the Dr. Joseph plastic surgery clinic regarding the evaluation of the satisfaction of patients who have undergone some type of surgical intervention within it in order to achieve Loyalty to current clients and get a greater number of clients to increase the current database that the clinic manages. A methodology based on the use of a mixed approach was used, the research techniques were descriptive and documentary. The study was carried out by collecting data that was obtained especially with patients who had undergone various aesthetic interventions from whom very important information was obtained related to various factors such as communication and empathy of medical personnel, the degree of information provided before surgery, the quality of postoperative care, the perception of patients regarding the results achieved, in order to know the satisfaction and experience that patients have had within the clinic. Through all the information that could be collected, it was possible to issue a final report with the background of the investigation and with a set of strategies that are proposed in order to increase patient satisfaction, strengthen the reputation and success of the clinic. plastic surgery of Dr. Joseph Duarte in a market that is becoming more competitive every day.